2015
DOI: 10.1017/s1368980015001251
|View full text |Cite
|
Sign up to set email alerts
|

Empirically derived dietary patterns and incident type 2 diabetes mellitus: a systematic review and meta-analysis on prospective observational studies

Abstract: Objective: To systematically review prospective cohort studies about the association between dietary patterns and type 2 diabetes mellitus (T2DM) incidence, and to quantify the effects using a meta-analysis. Design: Databases such as PubMed, ISI Web of Science, SCOPUS and Google Scholar were searched up to 15 January 2015. Cohort studies which tried to examine the association between empirically derived dietary patterns and incident T2DM were selected. The relative risks (RR) and their 95 % confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 39 publications
7
49
0
1
Order By: Relevance
“…Meta-analyses assessing the role of intake of milk and dairy products on risk of type 2 diabetes have consistently found no or a slight beneficial effect of dairy intake on diabetes risk (1215). This is consistent with a Mendelian randomisation study using genetic polymorphisms for the lactase gene, which showed that milk intake assessed by lactose tolerance was not associated with risk of type 2 diabetes or obesity (16).…”
Section: Obesity and Type 2 Diabetesmentioning
confidence: 99%
“…Meta-analyses assessing the role of intake of milk and dairy products on risk of type 2 diabetes have consistently found no or a slight beneficial effect of dairy intake on diabetes risk (1215). This is consistent with a Mendelian randomisation study using genetic polymorphisms for the lactase gene, which showed that milk intake assessed by lactose tolerance was not associated with risk of type 2 diabetes or obesity (16).…”
Section: Obesity and Type 2 Diabetesmentioning
confidence: 99%
“…Clinical and epidemiological studies have suggested that these beneficial nutrients like calcium, potassium and vitamins, play important roles in the prevention and the inhibition of blood pressure elevation [51][52]. Thus, these foods with high content of calcium, potassium, and several vitamins may counteract the harmful effects of other unhealthy items loaded on western-style pattern, which may explain the result [53]. Secondly, the BMI has been adjusted as a potential confounder in included studies.…”
Section: Disscussionmentioning
confidence: 99%
“…Although there is no standard definition of a "healthful pattern", it shows that fruits and vegetables were part of all healthful patterns detected in these studies. Interestingly, a very recent meta-analysis of 10 prospective studies concluded that a reduced risk of 14% may be achieved when adopting a healthful pattern consisting of fruits, vegetables, and whole grains [15]. These results further confirm the existence of a healthful, antidiabetic vegetarian-based diet.…”
Section: Discussionmentioning
confidence: 68%
“…Irrespective of the method applied, the results of studies on the relation of diet to risk of diabetes are inconsistent. A meta-analysis of 10 prospective studies, in which Caucasians, Africans, Hispanics, and Chinese were equally represented, concluded that "healthful" patterns, consisting of fruits, vegetables, and whole grain products, may reduce diabetes risk by 14%, whereas "unhealthful" patterns, including high contents of red and processed meat, high-fat dairy, and refined grains, may increase the risk by 30% [15]. However, a very recent casecontrol study did not find a significant association between healthful dietary patterns and diabetes risk [16].…”
Section: Introductionmentioning
confidence: 99%